2014
DOI: 10.5115/acb.2014.47.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saffron (Crocus sativusL.) on sodium valporate induced cytogenetic and testicular alterations in albino rats

Abstract: The present study investigated the cytogenetic and testicular damage induced by the antiepileptic drug, sodium valporate (SVP) in albino rats and the effect of saffron aqueous extracts. Treating rats with SVP caused a significant increase in the chromosomal aberrations either structural or numerical and decreased the mitotic index. Besides, animals administered SVP showed DNA damage appeared in the single strand breaks (comet assay). Testis of SVP-treated rats showed many histopathological changes. A significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
(42 reference statements)
3
20
0
Order By: Relevance
“…In consistency to other reports (Sakr et al, 2014;Hamza & Amin, 2007), our results also demonstrated that VPA treatments affect the weighs of body, testis, epididymis plus vas deferens and seminal vesicle, respectively (Table II). These adverse effects of VPA treatment include reductions of sperm concentration and seminiferous tubule diameters (Khan et al, 2011;Bairy et al;Krogenase et al, 2008;Svenberg Roste et al, 2002;Nishimura et al 2000).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In consistency to other reports (Sakr et al, 2014;Hamza & Amin, 2007), our results also demonstrated that VPA treatments affect the weighs of body, testis, epididymis plus vas deferens and seminal vesicle, respectively (Table II). These adverse effects of VPA treatment include reductions of sperm concentration and seminiferous tubule diameters (Khan et al, 2011;Bairy et al;Krogenase et al, 2008;Svenberg Roste et al, 2002;Nishimura et al 2000).…”
Section: Discussionsupporting
confidence: 81%
“…In experimental animals, VPA not only significantly decreases FSH, LH, and testosterone levels but also damages testicular tissue (Khan et al, 2011;Bairy et al, 2010;Krogenase et al, 2008;Hamza & Amin, 2007;Svenberg Roste et al, 2002;Nishimura et al, 2000). Currently, many medicinal plants have been used in searching for alternative treatments to prevent such side effects of VPA administration (Sakr et al, 2014;Hamza & Amin). Although, Momordica cochinchinesis (MC) has been demonstrated to have antioxidant activities and various phyto-therapeutic properties, the preventive effects on adverse male reproductive parameters and testicular damage have never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Besides such protective effects, recent study has shown for the first time about preventive property of MCP on male reproductive impairment of VPA-treated rats. Previous reports showed the increasing of testicular malondialdehyde (MDA) level in rats induced by VPA (Hamza & Amin;Sakr et al;Iamsaard et al, 2017b). Indeed, the increased MDA level in VPA testis was reduced by treatments with many medicinal plant extracts possessing antioxidant activity (Hamza & Amin;Iamsaard et al, 2015;Iamsaard et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported to have adverse effects such as decreasing of sex hormones and sperm qualities (Nishimura et al, 2000;Herzog et al, 2004;Hamza & Amin, 2007;Khan et al, 2011;Iamsaard et al, 2017a,b;Sukhorum & Iamsaard, 2017). Currently, herbal medicines have been studied for searching of alternative VPA treatments (Sakr et al, 2014;Iamsaard et al, 2015Iamsaard et al, , 2017bSukhorum et al, 2016). activity (Ghous et al, 2015), antidiabetic property (Blum et al, 2012), and anticancer property (Lee-Huang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…To prevent such side effects, many herbal medicines studies have been searching for alternative VPA treatments (Sakr et al, 2014;Hamza & Amin). Phyllanthus emblica L. (PE) or Thai-Makham Pom is a famous plant recently used as traditional medicine for many properties.…”
Section: Introductionmentioning
confidence: 99%